Manajemen Organisasi Dakwah Berbasis Kepemimpinan Situasional dalamPengelolaan Pondok Pesantren Kontemporer di Kabupaten Cianjur - Al Jufri, Lulu (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
The purpose of this study was to determine the level of maturity of the board members of Al Jufriyah Islamic Boarding School, leadership behavior, and situational leadership style in improving the quality of management of Al Jufriyah Islamic Boarding School. The theory used in this research is Hersey and Blanchard's theory of situational leadership. The method used in this study is a descriptive method through a qualitative approach which aims to describe and describe situational leadership in improving the quality of the management of Islamic Boarding Schools at Al Jufriyah Islamic Boarding School Cianjur with the process of observation, interviews and documentation studies. The results of this study were the maturity of the board members which were divided into two levels, namely low to medium and medium to high maturity levels were assessed. Then the leadership behavior in the management of Al Jufriyah Islamic Boarding School is task-oriented and relationship-oriented with members of the board. These two aspects present a situational leadership style including the style of instruction, consultation and participation.